Burkitt-like lymphoma with 11q aberration in a patient with AIDS and a patient without AIDS: Two cases reports and literature review - Wang Jing; Ma Li; Guo Jianghong; Xi Yanfeng; Xu Enwei (Open Medicine, 2021)
The aim of this study is to evaluate the clinicopathological features and the treatment of the Burkitt-like lymphoma with 11q aberration.